Excel 2013 introduction - Conway, Pamela; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"Microsoft Excel is one of the major workhorses in the Microsoft Office suite of applications and arguably the most widely-used Office product. A solid understanding of how to use this program is vital to nearly everyone in most industries today. This course is designed specifically to teach you the fundamentals of Excel and give you the skills you need to begin to create and manipulate worksheets. Specifically, you will understand how to create, save, enter data, and print spreadsheets in addition to learning how to create formulas and use functions to calculate in Excel. You will learn how to format spreadsheets, manipulate columns and rows, add headers and footers, and use page setup options to prepare them for printing. You will also learn how to handle large worksheets or multiple workbooks and use collaboration tools to work in conjunction with other users."--Resource description page.
Title from resource description page (Safari, viewed August 31, 2016).
Presenter, Pamela Conway.
Keywords: Microsoft Excel (Computer file); Electronic books